Relationship among Room Head's Leadership Style and Work Motivation with Nurses' Performance in Inpatient Room at AN-NISA Hospital Tangerang - Alpan Alpan; Nining Sriningsih; Ummi Giyanti (Universitas Muhammadiyah Tangerang, 2019)
In the hospital, nursing staff are the greatest number of hospital human resource and the longest staff who interact with clients. Nursing practice standards, include the standard of care and the professional performance standard that are use as evaluations in assessment nursing care who carry out by nurses. Performance or work performance comes from job performance word (work performance or real achievement someone has ever achieved). The factors that can affect on someone performance, are individual factors: abilities, skills, family background, work experience, social level and demography factor; psychological factors: perception, role, attitude, personality, motivation, and job satisfaction; organizational factors: organizational structure, job design, and leadership. To getting nurses with good performance, hospital need a leader who can understand the nurses' necessary and can provides good environmental assistance to make nurses feel motivated. This study aims to determine the relationship between room head's leaderschip style and work motivation in the inpatient room of AN-NISA Hospital, Tangerang. The research design used is a quantitative correlation with a cross-sectional approach. The sample in this study is organizer nurses in the inpatient room of AN-NISA Hospital in Tangerang and using purposive sampling technique with 83 respondents. Analysis technique using Chi-square test. The results showed that the dominant style of leadership in inpatient room of AN-NISA Hospital Tangerang is democratic style (48.2%). There is a relationship between the room head's leadership style and the performance of nurses (p.value = 0.033) and there is a relationship between work motivation and nurse performance (p. Value = 0.019). It is hoped that this research can be used as a material for evaluating hospitals regarding the leadership style of the head of the room, work motivation and performance of the nurse nurses to be able to maintain and improve the performance of nurses.